KINETICS PARAMETERS AND SHORT CHAIN FATTY ACIDS PROFILE OF THERMOTOLERANT LACTIC ACID BACTERIA WITH DIFFERENT CARBON SOURCES - DÍAZ-VELA M.Sc., Juan; MAYORGA-REYES Ph.D., Lino; TOTOSAUS S. Ph.D., Alfonso; PÉREZ-CHABELA Ph.D., Lourdes (Vitae, 2013)
Background: Prebiotics are substances obtained from vegetable sources which are digestible in the colon where is situated most of the intestinal flora. The chicory inulin and agave are used as prebiotics in different foods, providing benefits by increasing the beneficial microbial flora. Objectives: The aim of this study was to determine the effect of different carbon sources, such as inulin from agave, chicory, or orange albedo on the kinetic parameters and the profile of short chain fatty acids of lactic acid bacteria. Methods: Proximate analysis (moisture, protein, pH, ash, ether extract and total fiber) of orange albedo, agave inulin and chicory inulin was performed. Fermentation batches (12 h) were performed with two lactic acid bacteria, P. pentosaceus and A. viridans, employing chicory (CI), agave inulin (AI), and orange albedo (OA) as carbon source at different concentrations of 0.5, 1.0 and 1.5% (w/v), against glucose as control. The production of short chain fatty acids (SCFA) was performed using the HPLC technique (lactic acid) and gas chromatography (acetic, propionic and butyric acids). The results were analyzed using analysis of variance (ANOVA) and the difference between means was performed using a Tukey means analysis (α= 0.05). Results: OA showed a significantly (P < 0.05) higher moisture, ash, ether extract and total fiber, while AI had the highest percentage of protein and a higher pH (P < 0.05). For both strains, maximum growth was observed with 1.0% CI (P < 0.05), being lactic acid the major metabolite produced. With 1.0% OA, both strains showed shorter duplication time, and a higher lactic, acetic and butyric acids production (P < 0.05). Conclusions: By using OA, in the present experimental conditions, were obtained lower generation times compared with inulins, and increased production of organic acids, from which we conclude that the OA may be regarded as a potential prebiotic.